The effect of the New Silk Road railways on aggregate trade volumes between China and Europe - Yuan Li; Kierstin Bolton; Theo Westphal (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2016)
"One Belt, One Road" is an extensive and complex initiative whose potential effect and influence are still currently pending for answers. This paper addresses the following research question: What is the effect of the New Silk Road intercontinental railways on the trade between China and its trading partners in Central Asia and Europe? We focus on nine railway lines connecting Europe and China, which started operations between 2011 and 2015. The countries trade patterns with railway connections to China are then compared to the countries without railway connections to China. We find the intercontinental railways have a positive effect on Chinas exports to its trading partners in Central Asia and Europe, especially concerning exports of manufactured goods, machinery and transport equipment, and miscellaneous manufactured articles. Moreover, the intercontinental railways have a positive effect on Chinas imports of food and live animals from its trading partners.
Keywords: F02; F14; R4; 330; One Belt; One Road; trade; transportation cost; weapons of the rich; everyday forms of policy influence